LANDREFORM DAN KETIMPANGAN AGRARIA: STUDI KASUS KONFLIK MASYARAKAT AWYU MELAWAN PERLUASAN PERKEBUNAN SAWIT DI PAPUA SELATAN - Nugraha, Riko (Tribuere, 2023)
This article examines the agrarian conflict between the Indigenous Awyu people in South Papua and PT Indo Asiana Lestari (IAL) within the framework of Indonesia’s land reform policy. The study highlights the weak protection of customary land rights (hak ulayat) and the violation of the Free, Prior, and Informed Consent (FPIC) principle during the granting of environmental permits and palm oil plantation concessions covering 36,000 hectares of Awyu customary forests. Using a normative juridical approach combined with case study analysis, this research reviews relevant agrarian, forestry, environmental, and Papua Special Autonomy laws. The findings reveal manipulative practices in Environmental Impact Assessment (AMDAL) documentation, overlapping institutional authorities, and the dominance of economic interests over the protection of Indigenous rights and environmental sustainability. This conflict reflects structural inequality in land reform implementation and indicates the urgent need for agrarian policy reform that positions Indigenous peoples as primary decision-makers, alongside strengthening oversight mechanisms to prevent future violations of customary land rights.